Prioritization of Investment Alternatives for a Hospital by Using Neutrosophic CODAS Method - Bolturk, Eda; Karasan, Ali (OLD CITY PUBLISHING INC, 2019)
Hospital investment analysis is significant analysis for decision making. There are numerous criteria are effective about investment selection in hospital. Neutrosophic sets are characterized by three paramaeters which are truth-membership (T) indeterminacy-membership (I), and falsity-membership (F). COmbinative Distance-based ASsessment (CODAS) method which is a new multi criteria decision making (MCDM) technique. In this study, we analyze investment analysis for hospitals with interval-valued neutrosophic CODAS method. The same problem is solved with interval-neutrosophic TOPSIS. The results of interval-valued neutrosophic CODAS and interval-valued neutrosophic TOPSIS are compared and the suggestions for future work about investment analysis in conclusion are presented.
Keywords: CODAS; neutrosophic sets; investment selection; investment in hospital; SITE SELECTION; AHP; TOPSIS; Computer Science; Science & Technology - Other Topics